Portfolio Book of Great Indian Business Stories: Riveting Tales of Business Leaders and Their Times - Penguin Books (Bharat Penguin, 2015)
The Portfolio Book of Great Indian Business Stories contains excerpts from a selection of the finest business books published by Penguin Portfolio. This anthology features snippets from the lives of some of the most eminent business leaders India has seen-M.S. Oberoi, Ratan Tata, Aditya Birla and Rahul Bajaj, among others. There are tales of outstanding successes, crushing failures, extraordinary challenges and relentless determination, some of which chronicle the times when these legends were just simple businessmen trying to make a mark. The grit and ruthless persistence of these men defined who they were and the legacies they left behind.
Keywords: Sociology & Economics -- Sociology & Economics; Business -- Business